From Genre Awareness to Argumentative Sophistication: A Systematic Review of Rhetorical Competence Development in EFL Academic Writing - Jusak Patty; Marles Yohannis Matatula (International Journal of Multidisciplinary Approach Research and Science, 2026)
This systematic review synthesizes 42 empirical studies retrieved from a single database (Scopus) published from January 2020 to April 2026 to construct a developmental account of rhetorical competence in EFL academic writing. Moving beyond the established finding that genre-based instruction improves writing quality, the review examines the phases through which rhetorical competence appears to develop and the conditions that mediate its progression. Using thematic synthesis, three developmental phases are identified: genre consciousness, structural control, and argumentative sophistication—spanning learners' progression from recognizing genre conventions to acquiring discourse resources and ultimately developing epistemic stance management, multilayered argumentation, and rhetorical agency. This review finds that each phase transition requires qualitatively different instructional conditions and a progressively greater contribution from the learner's agentive engagement, with gains in genre recognition not automatically translating into discourse-level control, nor discourse-level control automatically yielding argumentative sophistication. Five mediating conditions emerged as recurring patterns: scaffolding quality, metalinguistic explicitness, learner agentive engagement, technological and multimodal mediation, and cross-cultural and L1 rhetorical influence. The model is offered as empirically grounded hypotheses rather than a validated developmental theory. Limitations include reliance on a single database, regional concentration in East and Southeast Asia, and the absence of longitudinal evidence. Future research should prioritize longitudinal designs, geographical diversification, and culturally responsive assessment frameworks. This study contributes a phase-sensitive developmental framework that reframes rhetorical competence as a layered construct developing through different mechanisms at different rates, shifting the analytical lens from whether genre-based instruction works toward how and under what conditions rhetorical development progresses.